Aedes albopictus in the United States: Ten-Year Presence and Public Health Implications - Chester G. Moore; Carl J. Mitchell (Emerging Infectious Diseases, 1997)
Since its discovery in Houston, Texas, in 1987, the Asian "tiger mosquito" Aedes albopictus has spread to 678 counties in 25 states. This species, which readily colonizes container habitats in the peridomestic environment, was probably introduced into the continental United States in shipments of scrap tires from northern Asia. The early pattern of dispersal followed the interstate highway system, which suggests further dispersal by human activities. The Public Health Service Act of 1988 requires shipments of used tires from countries with Ae. albopictus to be treated to prevent further importations. Given the extensive spread of the mosquito in the United States, it is questionable whether such a requirement is still justified. Ae. albopictus, a major biting pest throughout much of its range, is a competent laboratory vector of at least 22 arboviruses, including many viruses of public health importance. Cache Valley and eastern equine encephalomyelitis viruses are the only human pathogens isolated from U.S. populations of Ae. albopictus. There is no evidence that this mosquito is the vector of human disease in the United States.